CXCL9: evidence and contradictions for its role in tumor progression. (10th October 2016) - Ding, Qiang; Lu, Panpan; Xia, Yujia; Ding, Shuping; Fan, Yuhui; Li, Xin; Han, Ping; Liu, Jingmei; Tian, Dean; Liu, Mei
Abstract: Chemokines are a group of low molecular weight peptides. Their major function is the recruitment of leukocytes to inflammation sites, but they also play a key role in tumor growth, angiogenesis, and metastasis. In the last few years, accumulated experimental evidence supports that monokine induced by interferon (IFN)‐gamma (CXCL9), a member of CXC chemokine family and known to attract CXCR3‐ (CXCR3‐A and CXCR3‐B) T lymphocytes, is involved in the pathogenesis of a variety of physiologic diseases during their initiation and their maintenance. This review for the first time presents the most comprehensive summary for the role of CXCL9 in different types of tumors, and demonstrates its contradictory role of CXCL9 in tumor progression. Altogether, this is a useful resource for researchers investigating therapeutic opportunities for cancer. Abstract : This review for the first time presents the most comprehensive summarization of the role of CXCL9 in many types of tumor, and demonstrates the contradictory role of CXCL9 in tumor progression, which could be a useful resource providing rationale and support for future therapeutic opportunities for cancer.